2018
DOI: 10.1039/c7cp08677f
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric study of water's two glass transitions in the presence of LiCl

Abstract: Based on calorimetric data we show that water's two distinct glass transitions can be accessed up to the endpoint in dilute LiCl solutions. By contrast, in pure water both endpoints are masked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…The former value is in agreement with the one published by Amann-Winkel et al (4.8 J K −1 mol −1 ) [14]. Please note that Ruiz et al have observed a spike as part of the glass transition in eHDA [15]. They have suggested the spike to be caused by adiabatic cooling caused by the 25% expansion at the polyamorphic transition.…”
Section: Differential Scanning Calorimetrysupporting
confidence: 91%
See 2 more Smart Citations
“…The former value is in agreement with the one published by Amann-Winkel et al (4.8 J K −1 mol −1 ) [14]. Please note that Ruiz et al have observed a spike as part of the glass transition in eHDA [15]. They have suggested the spike to be caused by adiabatic cooling caused by the 25% expansion at the polyamorphic transition.…”
Section: Differential Scanning Calorimetrysupporting
confidence: 91%
“…b Ruiz et al [15] suggested 2.3 AE 0.5 J K −1 mol −1 on the basis of the first plateau in the c p curve that is not observed in Fig. 7.…”
Section: Isotope Effect On δC P and On Timescales Near The Glass Tmentioning
confidence: 92%
See 1 more Smart Citation
“…20 The presence of inorganic salts offers an attractive route to studying the amorphous forms of aqueous solutions, as, compared to pure water, these salts lower the homogeneous crystallization temperature and (at high concentrations) increase the glass transition temperature; thus, the ice crystallization is often suppressed. 6,[21][22][23] All alkali chloride solutions nevertheless exhibit a non-glass forming region, where standard cooling rates of up to about 1000 K min −1 are not sufficient to facilitate vitrification. [23][24][25] Such a scheme usually accompanies dilute solutions, the ones far below the eutectic concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is supporting evidence for polymorphism in water (1)(2)(3)(4)(5)12), the debate is still continuing for LLT in real water because of the experimental difficulty in accessing it in pure water (recent efforts to access LLT of pure water from the low-temperature side) (4,(13)(14)(15)(16)(17). There have also been efforts to access LLT of water by using aqueous solutions (18)(19)(20)(21)(22)(23)), yet which is often controversial. Thus, an unambiguous example of LLT is highly desirable for establishing its presence firmly.…”
mentioning
confidence: 99%